Clinical categories of exaggerated skin reactions to mosquito bites and their pathophysiology. Issue 3 (June 2016) - Tatsuno, Kazuki; Fujiyama, Toshiharu; Matsuoka, Hiroyuki; Shimauchi, Takatoshi; Ito, Taisuke; Tokura, Yoshiki
Abstract: Mosquito bites are skin irritating reactions, which usually resolve spontaneously without intensive medical care. However, in certain situations, mosquito bites may form a more vicious reaction, sometimes accompanying fever and systemic symptoms. In such cases, the presence of rare hematological disorders, abnormalities in eosinophils and/or association with Epstein-Barr virus (EBV) may underlie. Importantly, hypersensitivity to mosquito bites (HMB), which is characterized by necrotic skin reactions to mosquito bites with various systemic symptoms, is often observed in association with EBV infection and natural killer (NK) cell lymphoproliferative disorder. Exaggerated skin reaction to mosquito bites is also seen in Wells' syndrome. While strong Th2-skewing immune dysregulation is apparent in the patients, they also show robust CD4 + T cell proliferation in response to mosquito salivary gland extracts, indicating close association between Wells' syndrome and mosquito bites. Similar skin reaction to mosquito bites is also noticed in certain types of B cell neoplasm, although the role of B cells in this peculiar reaction to mosquito bites is yet to be elucidated. In this review, we will discuss the current knowledge of exaggerated reaction toward mosquito bites seen in conjunction with these unique hematological disorders, and examine the scientific studies and observations reported in previous literatures to organize our current understanding of the pathogenesis of this distinct disorder.